Paleogeographic controls on the onset of the Antarctic circumpolar current. Issue 19 (1st October 2013) - Hill, Daniel J.; Haywood, Alan M.; Valdes, Paul J.; Francis, Jane E.; Lunt, Daniel J.; Wade, Bridget S.; Bowman, Vanessa C.
Abstract [1] Development of the Antarctic Circumpolar Current (ACC) during the Cenozoic is controversial in terms of timing and its role in major climate transitions. Some propose that the development of the ACC was instrumental in the continental scale glaciation of Antarctica and climate cooling at the Eocene/Oligocene boundary. Here we present climate model results that show that a coherent ACC was not possible during the Oligocene due to Australasian paleogeography, despite deep water connections through the Drake Passage and Tasman Gateway and the initiation of Antarctic glaciation. The simulations of ocean currents compare well to paleoenvironmental records relating to the physical oceanography of the Oligocene and provide a framework for understanding apparently contradictory dating of the initiation of the ACC. We conclude that the northward motion of the Australasian land masses and the reconfiguration of the Tasman Seaway and Drake Passage are necessary preconditions for the formation of a strong, coherent ACC.